Sound frequency affects speech emotion perception: results from congenital amusia - Lolli, Sydney; Lewenstein, Ari D.; Basurto, Julian; Winnik, Sean; Loui, Psyche (Frontiers in Psychology, 2015)
Congenital amusics, or “tone-deaf” individuals, show difficulty in perceiving and producing small pitch differences. While amusia has marked effects on music perception, its impact on speech perception is less clear. Here we test the hypothesis that individual differences in pitch perception affect judgment of emotion in speech, by applying band-pass filters to spoken statements of emotional speech. A norming study was first conducted on Mechanical Turk to ensure that the intended emotions from the Macquarie Battery for Evaluation of Prosody (MBEP) were reliably identifiable by US English speakers. The most reliably identified emotional speech samples were used in in Experiment 1, in which subjects performed a psychophysical pitch discrimination task, and an emotion identification task under band-pass and unfiltered speech conditions. Results showed a significant correlation between pitch discrimination threshold and emotion identification accuracy for band-pass filtered speech, with amusics (defined here as those with a pitch discrimination threshold > 16 Hz) performing worse than controls. This relationship with pitch discrimination was not seen in unfiltered speech conditions. Given the dissociation between band-pass filtered and unfiltered speech conditions, we inferred that amusics may be compensating for poorer pitch perception by using speech cues that are filtered out in this manipulation.